Biliary Ascariasis: Overall Perspective of Management - Hoque, Md Saiful; Chowdhury, Tahmina Akther; Haider, Salauddin Mohammed Ali; Qurashi, Sabrina Akhter; Nath, Sabuj Kanti (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: One of the common cause of admission in surgical ward with acute abdomen in Asian subcontinent is Biliary Ascariasis.The causative agent, Ascarias lumbricoides is distributed throughout the tropics & subtropics & mostly prevent is developing country due to unhygienic livelihood. This study deals with management of Biliary Ascariasis demonstrating the effectiveness of only conservative management in acute condition. Materials and methods: This was an analytical study where 47 patients diagnosed as a case of Biliary Ascariasis were observed & managed accordingly. Complete history, diagnostic tool, complication of Ascarisis & treatment modality were analysed. Result: Here we documented 47 patients throughout the period October-2018 to September -2019 age limit is 13 yrs to 70 yers. Out of which female patient was 78.72% where male was 21.27%. Among female patient 10.63% were pregnant at the time of presentation. 100% patient present with biliary colic, 57.44% had associated nausea & vomiting 38.99% patient present as a case of cholecystitis. Cholangitis developed was 8.5% patient, 8.5% had obstructive jaundices, 4.2% developed liver abscess, 6.38% pancreatitis, 10.63% got cholelithiasis & 8.51% develop chololadocholithiasis &/ or hepaticolithiasis. USG & CBC was advised for all patient as standard diagnostic tool. During conservative treatment endoscopy was advised to all, only 63.82% was able to do this & successful extraction of worm was possible in 26.02%.70% improved by conservative treatment & ERCP required in 10.63%.Surgery for exploring CBD was done in 1 patient (2.1%). 34.02% patient had H/O recurrent attack. 17.02% patient underwent previous endoscopic procedure & 8.51% ERCP procedure. Before discharge review USG found in 68.08% patient with evidence of clear CBD & then discharged with advice of taking Antihelmintic therapy in 2 months interval. Conclusion: Maintenance of hygienic & regular anthelmintic therapy is all prevention of occurance & complication. only conservative management with or without minimal invasive endoscopic retrieval of worm is very much effective for improvement of symptoms. JCMCTA 2019 ; 31 (1) : 9-12